Real or natural number interpretation and their effect on complexity - Bonfante, Guillaume; Deloup, Florian; Henrot, Antoine (Theoretical computer science, 2015)
Interpretation methods have been introduced in the 70s by Lankford [1] in rewriting theory to prove termination. Actually, as shown by Bonfante et al. [2], an interpretation of a program induces a bound on its complexity. However, Lankford's original analysis depends deeply on the Archimedean property of natural numbers. This goes against the fact that finding a real interpretation can be solved by Tarski's decision procedure over the reals (as described by Dershowitz in [3]), and consequently interpretations are usually chosen over the reals rather than over the integers. Doing so, one cannot use anymore the (good) properties of the natural (well-)ordering of N used to bound the complexity of programs. We prove that one may take benefit from the best of both worlds: the complexity analysis still holds even with real numbers. The reason lies in a deep algebraic property of polynomials over the reals. We illustrate this by two characterizations, one of polynomial time and one of polynomial space.